On Certain Sufficient Condition Involving Gaussian Hypergeometric Functions - H. Silverman; Thomas Rosy; S. Kavitha (International Journal of Mathematics and Mathematical Sciences)
The authors define a new subclass of 𝒜 of functions involving complex order in the open unit disk 𝕌. For this new class, we obtain certain inclusion properties involving the Gaussian hypergeometric functions.